Strategi Konten Kreator dalam Mengoptimalkan Pendapatan Melalui Youtobe Shopee Affiliate - Amriwan, Azis; Mahmud, Imam; Ananda Salsabila, Ratu; Anisa, Nur (Prodi Sosiologi Universitas Mataram, 2024)
YouTube shopping affiliate is a feature released by YouTube to provide the opportunity to earn additional income for YouTube channel owners who meet the requirements. The program was created by connecting products that are bought and sold on the Shopee marketplace to be promoted through videos made by content creators on YouTube by adding tags to them in the videos. This research uses a literature study method with a qualitative approach to find out strategies for optimizing income through video programs created by content creators. The research results show that making videos, writing descriptions, channel names, tags, and video duration have a big influence on someone's behavior in buying the recommended product. The existence of social action on the YouTube shopping affiliate program is also carried out through an approach in the analysis of dromological theory, including regarding flow, trajectory and duration. In the process, research findings illustrate that the concept of faster digital flow allows someone to be able to follow trends based on videos that match someone's behavior to be encouraged to buy recommended products.